Wing patterning genes of Nilaparvata lugens identification by transcriptome analysis, and their differential expression profile in wing pads between brachypterous and macropterous morphs - Kai-yin LI; Ding-bang HU; Fang-zhou LIU; Man LONG; Si-yi LIU; Jing ZHAO; Yue-ping HE; Hong-xia HUA (Journal of Integrative Agriculture)
The brown planthopper, Nilaparvata lugens is an economically important pest on rice plants. This species produces macropterous and brachypterous morphs in response to environmental cues, which makes it very difficult to control. The molecular basis of wing patterning in N. lugens is still unknown. It is necessary to identify wing patterning genes of N. lugens, and also to clarify the expression differences of wing patterning genes between macropterous and brachypterous morphs. High-throughput deep sequencing of transcriptome of N. lugens wing pad yielded 116 744 580 raw reads and 113 042 700 clean reads. All the reads were assembled into 55 963 unigenes with an average length of 804 bp. With the E-value cut-off of 1.0E−5,18 359 and 2 883 unigens had hits in NCBI-NR (NCBI non-redundant protein sequences) and NCBI-NT (NCBI nucleotide sequences) databases, respectively. A total of 16 502 unigenes were assigned to GO (gene ontology) classification, 9 709 ungenes were grouped into 26 COG (cluster of orthologous groups of proteins) classifications, and 6 724 unigenes were assigned to different KEGG (Kyoto encyclopedia of genes and genomes) pathways. In total, 56 unigenes which are homologous to wing patterning genes of Drosophila melanogaster or Tribolium castaneum were identified. Out of the 56 unigenes, 24 unigenes were selected, and their expression levels across the five nymphal stages between macropterous strain and brachypterous strain were examined by qRT-PCR. Two-way ANOVA analysis showed that development stage had significant effects on the expression level of all the 24 genes (P<0.05). The expression levels of 8 genes (Nlen, Nlhh, Nlsal, NlAbd-A, Nlwg, Nlvg, Nlexd and NlUbx) were significantly affected by wing morph. This is the first transcriptome analysis of wing pads of hemimetabolous insect, N. lugens. The identified wing patterning genes would be useful resource for future exploration of molecular basis of wing development. The 8 differentially expressed wing patterning genes between macropterous strain and brachypterous strain would contribute to explain molecular mechanism of wing-morph differentiation in N. lugens.